2020
DOI: 10.1101/2020.09.24.20201285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics, Management And Outcomes Of Critically Ill Covid-19 Patients Admitted To Icu In Hospitals In Bangladesh: A Retrospective Study

Abstract: Objectives: This study aimed to analyse the epidemiological and clinical characteristics of critical COVID-19 cases and investigate risk factors including comorbidities and age in relation with the clinical aftermath of COVID-19 in critical cases in Bangladesh. Methods: In this retrospective study, epidemiological and clinical characteristics, complications, laboratory results, and clinical management of the patients were studied from data obtained from 168 individuals diagnosed with an advanced prognosis of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…This is in agreement with a previous study which showed that more than half of participants with diabetes were worried about being affected by COVID-19 [25]. Research suggests that a substantial majority of hospitalized patients with COVID-19 are individuals with diabetes [43][44][45]. Diabetic patients have shown to be susceptible to life-threatening infections such SARs, MERs, H191, possibly as a result of a dysregulated immune response [45,46].…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with a previous study which showed that more than half of participants with diabetes were worried about being affected by COVID-19 [25]. Research suggests that a substantial majority of hospitalized patients with COVID-19 are individuals with diabetes [43][44][45]. Diabetic patients have shown to be susceptible to life-threatening infections such SARs, MERs, H191, possibly as a result of a dysregulated immune response [45,46].…”
Section: Discussionsupporting
confidence: 91%
“…However, the presence of hypertension was positively correlated with death, ICU care and severity [ 12 ]. Worth mentioning, hypertension has not been found to make any significant difference in the mortality rate among the critical COVID-19 cases in Bangladesh [ 16 ]. Data obtained from a study in the U.K. suggest that mortality rate does not increase with hypertension, while the presence of uncontrolled and controlled diabetes along with hypertension increases the risk 2.36 and 1.50 fold respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, a more extensive study on 72,314 patients with COVID-19 reported that the mortality rate in patients with diabetes was threefold compared to the mortality rate of COVID-19 in patients overall [ 15 ]. A previous study conducted in Bangladeshi on patients with COVID-19 admitted in ICUs found that over 50% of the patients (52.4%) seeking care in the ICUs had diabetes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In nine studies conducted in South Korea (n = 37,938) (70,(118)(119)(120)(121)(122)(123)(124)(125), the pooled prevalence was 5.4% (95 % CI, 2.3-9.6%). Data regarding asthma prevalence in people with COVID-19 in Canada ( 126), Brazil (127-129), India (130,131), Bangladesh (132,133), the Philippines (134), Japan (135,136), Africa (137)(138)(139)(140), Iran (141,142), Kuwait (143), Turkey (144)(145)(146), Israel (147)(148)(149), and Saudi Arabia (150) were relatively sparse, making them difficult to characterize by country, but they were generally within the range of the prevalences reported above.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%